Structural retrofitting of buildings: Turnbuckle exterior post tensioning - Lejano, Bernardo A. (Animo Repository, 2015)
Nowadays the problem of aging and deterioration of reinforced concrete buildings are eminent and due to excessive loading, the flexural performance and serviceability of structures are affected. The turnbuckle exterior post tensioning (T-EPT) is proposed as a retrofitting method wherein it was proven experimentally that it can be able to improve the serviceability and load carrying capacity of beams. A computer modeling method was developed to simulate the application of the T-EPT to full scale beam sections to determine its effectiveness with different cases. Different T-EPT configurations were modeled and the most efficient design that can be applied to structures was determined. Overall the T-EPT was effective in improving the serviceability and load carrying capacity of reinforced concrete beams.